Battery modules, battery packs and ceramic silicone foam sheets

By controlling the characteristics of the ceramicized silicone foam sheet, the problem of poor buffering performance when used between soft-packed batteries is solved, effective buffering, thermal insulation and fire protection is achieved, extending the service life of the battery cell and providing good thermal runaway protection.

CN119340589BActive Publication Date: 2025-04-18HUBEI XIANGYUAN HIGH-TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411867567.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

When used between soft-clad battery cells, the existing ceramicized silicone foam sheet has high strength but poor buffering performance, and cannot effectively absorb the volume expansion force of the battery cell, resulting in a shortening of the battery cell service life.

Method used

By controlling the foaming ratio of the ceramicized silicone foam sheet, the NMR lateral relaxation time T2, the porosity rate and thermal weight loss, it has the characteristics of small and suitable compression stress, it can effectively absorb the volume expansion force of the battery cell, and quickly form a hard ceramic body when thermal runaway occurs to prevent the flame from spreading.

Benefits of technology

It realizes the effective buffering, heat insulation and fire protection function of ceramicized silicone foam sheets in battery modules and battery packs, extends the service life of the battery cell, and provides good fire protection and heat insulation protection in the case of thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340589B_ABST
    Figure CN119340589B_ABST
Patent Text Reader

Abstract

The present invention discloses a battery module, a battery pack and a ceramic silicone foam sheet, belonging to the field of battery technology. The battery module comprises: more than two soft-pack battery cells and more than one ceramic silicone foam sheet, the ceramic silicone foam sheet is arranged between adjacent soft-pack battery cells; the ceramic silicone foam sheet has a foaming ratio of 3.6 to 6, a nuclear magnetic resonance transverse relaxation time T2 of 105 to 130 ms, an open porosity of ≥ 20%, and a thermal weight loss of 30 to 50%. The ceramic silicone foam sheet of the present invention has both high ceramic strength and a gentle compression stress-strain curve, and is suitable for use in battery modules and battery packs as a buffer, heat-insulating and fire-proof gasket between soft-pack battery cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery module, a battery pack and a ceramic silicone foam sheet. Background Art

[0002] Soft-pack batteries refer to batteries that use aluminum-plastic film as packaging materials. Soft-pack batteries have the advantages of light weight, low internal resistance, and good cycle performance. Moreover, the size and shape of soft-pack batteries can be flexibly designed according to actual needs, not limited to traditional round and square shapes.

[0003] During the charge and discharge process, the volume of the soft-pack battery will expand, resulting in an increase in the compressive stress of the soft-pack battery. The layers of material in the battery cell are excessively squeezed against each other, which increases the difficulty of lithium ions escaping and reduces the capacity of the battery cell.

[0004] When a soft-pack battery cell experiences thermal runaway, it will release heat and gas, which can cause electrical fires under high temperature and pressure. Currently, the temperature of ternary lithium batteries on the market can exceed 600°C after thermal runaway, and the temperature will rise further if an open flame is ignited. Generally, if the temperature in the battery pack exceeds 200°C, there is a risk of thermal runaway; if it exceeds 250°C, the risk is extremely high. The duration of thermal runaway of a single battery cell is usually less than 5 minutes.

[0005] Although soft-pack batteries have a lower risk of explosion after thermal runaway than metal-cased batteries, soft-pack batteries also need appropriate measures to prevent the spread of flames and protect adjacent batteries from thermal runaway when thermal runaway occurs.

[0006] If the existing ceramic silicone foam sheet is to have a higher porcelain strength, a higher proportion of powder needs to be added to the raw material. This makes the viscosity of the raw material higher, so that the foaming resistance of the raw material is larger, and finally the density of the ceramic silicone foam sheet is larger, the compression stress is larger, and the compression stress-strain curve is steep. If this ceramic silicone foam sheet is used as a buffer, heat insulation and fireproof gasket between soft-pack batteries, although it has a high porcelain strength and good fireproof performance, its buffering performance is poor and it cannot effectively absorb the volume expansion force of the soft-pack battery, which will reduce the service life of the battery. Summary of the invention

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a battery module, a battery pack and a ceramic silicone foam sheet. The ceramic silicone foam sheet of the present invention has the characteristics of high ceramic strength and a gentle compression stress-strain curve, and is suitable for use in battery modules and battery packs as a buffer, heat insulation and fireproof gasket between soft-pack battery cells.

[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a battery module, comprising: two or more soft-pack battery cells and one or more ceramic silicone foam sheets, wherein the ceramic silicone foam sheets are arranged between adjacent soft-pack battery cells; wherein the ceramic silicone foam sheet has a foaming ratio of 3.6 to 6, a nuclear magnetic resonance transverse relaxation time T2 of 105 to 130 ms, an open porosity of ≥20%, and a thermal weight loss of 30 to 50% after ablation at 800°C for 30 min;

[0009] The test conditions of the nuclear magnetic resonance transverse relaxation time T2 include: using CPMG pulse sequence excitation, the sensor frequency is 6.0 MHz, the pulse width D=4.5 μs, the echo time TE=120 μs, the number of 180° pulses is 1000, the repetition time is 1000 ms, the 90° pulse amplitude is -20 dB, and the 180° pulse amplitude is -14 dB;

[0010] The open porosity is calculated using the following formula:

[0011]

[0012] Wherein, χ is the open porosity of the ceramic silicone foam sheet, %; θ is the vacuum volume water absorption of the ceramic silicone foam sheet tested according to the method in Appendix B of GB / T 17794-2021; ρ1 is the density of the ceramic silicone foam sheet tested according to the method in GB / T 6343-2009, g / cm 3 ρ s The density of the surface of the ceramic silicone foam sheet tested according to method A in GB / T533-2008, g / cm 3 .

[0013] The second aspect of the present invention provides a battery pack, which includes: a box and a battery module; the box includes a module frame, a module cover, a wiring harness isolation plate and a liquid cooling plate; the battery module includes two or more soft-pack batteries and one or more ceramic silicone foam sheets, and the ceramic silicone foam sheets are arranged between adjacent soft-pack batteries; the battery module is arranged in the module frame, the module cover is arranged on the top of the battery module, the wiring harness isolation plate is arranged between the battery module and the module cover, the wiring harness isolation plate is provided with a busbar for connecting the soft-pack batteries, and the liquid cooling plate is arranged around the battery module; wherein the ceramic silicone foam sheet has a foaming ratio of 3.6~6, a nuclear magnetic resonance transverse relaxation time T2 of 105~130ms, an open porosity of ≥20%, and a thermal weight loss of 30~50% after ablation at 800°C for 30min;

[0014] The test conditions of the nuclear magnetic resonance transverse relaxation time T2 include: using CPMG pulse sequence excitation, the sensor frequency is 6.0 MHz, the pulse width D=4.5 μs, the echo time TE=120 μs, the number of 180° pulses is 1000, the repetition time is 1000 ms, the 90° pulse amplitude is -20 dB, and the 180° pulse amplitude is -14 dB;

[0015] The open porosity is calculated using the following formula:

[0016]

[0017] Wherein, χ is the open porosity of the ceramic silicone foam sheet, %; θ is the vacuum volume water absorption of the ceramic silicone foam sheet tested according to the method in Appendix B of GB / T 17794-2021; ρ1 is the density of the ceramic silicone foam sheet tested according to the method in GB / T 6343-2009, g / cm 3 ρ s The density of the surface of the ceramic silicone foam sheet tested according to method A in GB / T533-2008, g / cm 3 .

[0018] The third aspect of the present invention provides a ceramic silicone foam sheet, which has a foaming ratio of 3.6-6, a nuclear magnetic resonance transverse relaxation time T2 of 105-130ms, an open porosity of ≥20%, and a thermal weight loss of 30-50% after ablation at 800°C for 30 minutes;

[0019] The test conditions of the nuclear magnetic resonance transverse relaxation time T2 include: using CPMG pulse sequence excitation, the sensor frequency is 6.0 MHz, the pulse width D=4.5 μs, the echo time TE=120 μs, the number of 180° pulses is 1000, the repetition time is 1000 ms, the 90° pulse amplitude is -20 dB, and the 180° pulse amplitude is -14 dB;

[0020] The open porosity is calculated using the following formula:

[0021]

[0022] Wherein, χ is the open porosity of the ceramic silicone foam sheet, %; θ is the vacuum volume water absorption of the ceramic silicone foam sheet tested according to the method in Appendix B of GB / T 17794-2021; ρ1 is the density of the ceramic silicone foam sheet tested according to the method in GB / T 6343-2009, g / cm 3 ρ s The density of the surface of the ceramic silicone foam sheet tested according to method A in GB / T533-2008, g / cm 3.

[0023] According to a specific embodiment of the present invention, preferably, the three-point bending strength of the ceramicized silicone foam sheet after being ablated at 800° C. for 30 minutes is ≥8 MPa.

[0024] According to a specific embodiment of the present invention, preferably, the density of the ceramic silicone foam sheet is 200-500 kg / m 3 .

[0025] According to a specific embodiment of the present invention, preferably, the 10% compressive stress of the ceramic silicone foam sheet is 10-20 KPa, and the ratio of the 70% compressive stress to the 10% compressive stress is 20-30.

[0026] According to a specific embodiment of the present invention, preferably, the thickness of the ceramic silicone foam sheet is 1-15 mm.

[0027] According to a specific embodiment of the present invention, preferably, the average pore diameter of the ceramic silicone foam sheet is 0.2-1.0 mm.

[0028] According to a specific embodiment of the present invention, preferably, when one side of the ceramic silicone foam sheet is heated at 800°C for 5 minutes, the temperature of the other side thereof is ≤250°C, and the thermal insulation coefficient of the ceramic silicone foam sheet is ≥275°C / mm, wherein the thermal insulation coefficient = (the temperature of one side of the ceramic silicone foam sheet when heated at 800°C for 5 minutes - the temperature of the other side of the ceramic silicone foam sheet) ÷ the thickness of the ceramic silicone foam sheet.

[0029] According to a specific embodiment of the present invention, preferably, after one side of the ceramic silicone foam sheet is ablated with an acetylene-oxygen flame at 1300° C. for 10 minutes, no cracks appear on the other side thereof.

[0030] According to a specific embodiment of the present invention, preferably, the Shore A hardness of the ceramic silicone foam sheet is .

[0031] The present invention has at least the following beneficial effects:

[0032] The ceramic silicone foam sheet of the present invention has the characteristics of small and appropriate compressive stress and a gentle compressive stress-strain curve, which can effectively absorb the volume expansion force of the soft-pack battery cell, has better buffering performance, and can extend the service life of the battery cell. When the battery cell has thermal runaway, the ceramic silicone foam sheet of the present invention can form a ceramic body with high ceramic strength, which can prevent the spread of flames, slow down heat transfer, and protect adjacent batteries from thermal runaway. The ceramic silicone foam sheet of the present invention is suitable for use in battery modules and battery packs as a buffer, heat-insulating and fire-proof gasket between soft-pack batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the structure of a battery module for charge and discharge cycle testing in a specific implementation manner.

[0034] Explanation of the accompanying figures: 1-soft-pack battery cell; 2-plywood; 3-foam sheet sample; 4-pressure sensor; 5-fastener. DETAILED DESCRIPTION

[0035] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is now described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0036] <Ceramic Silicone Foam Sheet>

[0037] The invention provides a ceramic silicone foam sheet, wherein the foaming ratio of the ceramic silicone foam sheet is 3.6-6, for example, but not limited to 3.6, 4, 4.5, 5, 5.5 or 6; the nuclear magnetic resonance transverse relaxation time T2 of the ceramic silicone foam sheet is 105-130ms, for example, but not limited to 105ms, 110ms, 115ms, 120ms, 125ms or 130ms; the opening rate of the ceramic silicone foam sheet is ≥20%, for example, but not limited to 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%; and the thermal weight loss of the ceramic silicone foam sheet after ablation at 800° C. for 30 minutes is 30-50%, for example, but not limited to 30%, 35%, 40%, 45% or 50%;

[0038] The test conditions of the nuclear magnetic resonance transverse relaxation time T2 include: using CPMG pulse sequence excitation, the sensor frequency is 6.0 MHz, the pulse width D=4.5 μs, the echo time TE=120 μs, the number of 180° pulses is 1000, the repetition time is 1000 ms, the 90° pulse amplitude is -20 dB, and the 180° pulse amplitude is -14 dB;

[0039] The open porosity is calculated using the following formula:

[0040]

[0041] Wherein, χ is the open porosity of the ceramic silicone foam sheet, %; θ is the vacuum volume water absorption of the ceramic silicone foam sheet tested according to the method in Appendix B of GB / T 17794-2021; ρ1 is the density of the ceramic silicone foam sheet tested according to the method in GB / T 6343-2009, g / cm 3 ρ sThe density of the surface of the ceramic silicone foam sheet tested according to method A in GB / T533-2008, g / cm 3 .

[0042] The inventors conducted research on the foaming ratio, nuclear magnetic resonance transverse relaxation time T2 and porosity and unexpectedly found that by controlling the foaming ratio, nuclear magnetic resonance transverse relaxation time T2 and porosity within the scope of the present invention, the compressive stress of the ceramic silicone foam sheet can be small and appropriate, and the compressive stress-strain curve can be smooth.

[0043] Specifically, the present invention controls the foaming ratio so that the number of cells of the ceramic silicone foam sheet per monomer volume is appropriate. If the foaming ratio is greater than 6, the number of cells of the ceramic silicone foam sheet per monomer volume is too large, so that its 10% compression stress is too small; if the foaming ratio is less than 3.6, the number of cells of the ceramic silicone foam sheet per monomer volume is too small, so that its 10% compression stress is too large. At the same time, the present invention controls the foaming ratio within the above range so that the foam sheet has good thermal insulation performance.

[0044] In addition, the present invention controls the nuclear magnetic resonance transverse relaxation time T2 to 105-130ms, so that the ceramic silicone foam sheet has a suitable flexible segment. If the nuclear magnetic resonance transverse relaxation time T2 is less than 105ms, the flexible segments in the molecular structure of the ceramic silicone foam sheet are insufficient, so that its 10% compressive stress is too large; if the nuclear magnetic resonance transverse relaxation time T2 is greater than 130ms, the flexible segments in the molecular structure of the ceramic silicone foam sheet are too many, so that its 10% compressive stress is too small.

[0045] In addition, the present invention controls the open porosity to be above 20%, so that the open porosity, the foaming ratio and the transverse relaxation time T2 of the nuclear magnetic resonance produce a synergistic effect, and jointly affect the compressive stress of the ceramic silicone foam sheet, so that the 10% compressive stress of the foam sheet of the present invention is 10-20 KPa, and the ratio of the 70% compressive stress to the 10% compressive stress is 20-30. When the ratio is within the range of the present invention, the compressive stress-strain curve is gentle.

[0046] At the same time, the present invention further controls the thermal weight loss of the ceramicized silicone foam sheet to 30-50% after ablation at 800°C for 30 minutes, which can ensure that the foam sheet forms a hard and dense ceramic body after high-temperature ablation, has a high ceramic strength and low thermal expansion, so that the ceramic body has suitable integrity, so that it can better isolate the flame and slow down the heat transfer rate, and at the same time ensure that the density and compression stress of the foam sheet are in a suitable range. If the thermal weight loss is greater than 50%, the gap between the ceramic fillers of the foam sheet is too large, and it is difficult to form a hard and dense ceramic body after high-temperature ablation, and the ceramic strength is low; if the thermal weight loss is less than 30%, the force between the powders in the raw materials of the foam sheet is too strong, which hinders foaming, so that the density of the foam sheet is too high, the compression stress is too large, and the compression stress-strain curve is steep. Therefore, the present invention can make the compression stress of the foam sheet small and suitable by controlling the thermal weight loss in the above range, and the compression stress-strain curve is gentle, and has a high ceramic strength.

[0047] In summary, the present invention controls the foaming ratio, the nuclear magnetic resonance transverse relaxation time T2, the open porosity and the thermal weight loss within the above-mentioned ranges, so that the ceramic silicone foam sheet has a small and appropriate compressive stress, and at the same time, the compressive stress-strain curve is gentle, which can effectively absorb the volume expansion force of the soft-pack battery cell, has better buffering performance, and can extend the service life of the battery cell; and, the ceramic silicone foam sheet can quickly form a ceramic body when the battery cell has thermal runaway, has a high ceramic strength, can prevent the spread of flames, slow down the heat transfer rate, and protect adjacent batteries from thermal runaway.

[0048] In some embodiments, the three-point bending strength of the ceramicized silicone foam sheet after ablation at 800°C for 30 minutes is ≥8MPa, for example but not limited to 8MPa, 10MPa, 12MPa, 14MPa, 16MPa, 18MPa or 20MPa, etc. The present invention controls the three-point bending strength of the foam sheet after ablation within the above range, which produces a synergistic effect with the thermal weight loss of the foam sheet after ablation at 800°C for 30 minutes, so that the foam sheet has a higher ceramic strength, and the foam sheet is not burned through after being impacted by flames. At the same time, when one side of the foam sheet is heated at 800°C for 5 minutes, the temperature of the other side is ≤250°C, which can effectively block heat, thereby making the foam sheet have better fireproof and heat insulation effects. If the three-point bending strength of the foam sheet after being ablated at 800°C for 30 minutes is less than 8MPa, the amount of ceramic filler that can participate in the eutectic reaction in the raw materials of the foam sheet is insufficient, making the structure of the ceramic body formed by the foam sheet after high-temperature ablation not hard and dense enough, and it is easily burned through by flames and broken, and cannot play a role in fire prevention and heat insulation.

[0049] In some embodiments, the density of the ceramic silicone foam sheet is 200-500 kg / m 3, for example but not limited to 200kg / m 3 , 250kg / m 3 、300kg / m 3 、350kg / m 3 , 400kg / m 3 , 450kg / m 3 or 500kg / m 3 etc., preferably 250~350kg / m 3 If the density of the foam sheet is less than 200kg / m 3 , the compression stress of the foam sheet will be too low, and it will not be able to provide sufficient preload force to the battery cell. At the same time, it will not be able to effectively absorb the volume expansion force of the battery cell when the battery cell expands, which will reduce the service life of the battery cell. If the density of the foam sheet is higher than 500kg / m 3 If the density is too high, the compression stress of the foam sheet will be too large, causing excessive squeezing of the battery cell and reducing the service life of the battery cell. At the same time, excessive density will also reduce the thermal insulation performance of the foam sheet, and it will not be able to effectively protect the adjacent battery cells when thermal runaway occurs in the battery cell.

[0050] In some embodiments, the 10% compressive stress of the ceramic silicone foam sheet is 10-20KPa, such as 10KPa, 12KPa, 14KPa, 16KPa, 18KPa or 20KPa, etc.; and the ratio of the 70% compressive stress to the 10% compressive stress of the ceramic silicone foam sheet is 20-30, such as but not limited to 20, 22, 24, 26, 28 or 30, etc. The present invention controls the 10% compressive stress of the foam sheet and the ratio of the 70% compressive stress to the 10% compressive stress within the above range. When applied between battery cells, the present invention can provide a suitable pre-tightening force to the battery cell, and when the battery cell expands, it can effectively absorb the volume expansion force of the battery cell, has better buffering performance, and extends the service life of the battery cell. If the 10% compressive stress of the foam sheet and the ratio of 70% compressive stress to 10% compressive stress are higher or lower than the above range, the pre-tightening force of the foam sheet on the battery cell will be too large or too small, and it will not be able to effectively absorb the volume expansion force of the battery cell, which will reduce the service life of the battery cell.

[0051] In some embodiments, the thickness of the ceramic silicone foam sheet is 1 to 15 mm, for example but not limited to 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 10 mm or 15 mm, etc. If the thickness of the foam sheet is less than 1 mm, the foaming ratio of the foam sheet is too low and the density is difficult to control; if the thickness of the foam sheet is greater than 15 mm, the foaming of the foam sheet is uneven and the pores are too large.

[0052] In some embodiments, the average pore diameter of the ceramic silicone foam sheet is 0.2-1.0 mm, for example but not limited to 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm or 1.0 mm, etc. The present invention can further control the foam sheet to have a suitable compressive stress and ensure that the compressive stress-strain curve is gentle by controlling the average pore diameter of the foam sheet within the above range.

[0053] In some embodiments, when one side of the ceramic silicone foam sheet is heated at 800°C for 5 minutes, the temperature of the other side thereof is ≤250°C, such as but not limited to 250°C, 240°C, 230°C, 220°C, 210°C, 200°C, 190°C or 180°C, etc.; and the thermal insulation coefficient of the ceramic silicone foam sheet is ≥275°C / mm, such as but not limited to 275°C / mm, 280°C / mm, 285°C / mm, 290°C / mm, 295°C / mm or 300°C / mm, etc., wherein the thermal insulation coefficient = (the temperature of one side of the ceramic silicone foam sheet when heated at 800°C for 5 minutes - the temperature of the other side of the ceramic silicone foam sheet) ÷ the thickness of the ceramic silicone foam sheet. The present invention heats one side of the foam sheet at 800°C for 5 minutes, and the temperature of the other side and the thermal insulation coefficient of the foam sheet are within the above range, which can effectively block heat, so that the foam sheet has better fireproof and thermal insulation effects, and can effectively deal with the thermal runaway of ternary lithium batteries on the market. When applied between battery cells, if the battery cell on one side of the foam sheet has thermal runaway, the risk of thermal runaway of the battery cell on the other side of the foam sheet is greatly reduced due to the lower temperature and higher thermal insulation coefficient of the other side of the foam sheet, thereby protecting the adjacent battery cells.

[0054] In some embodiments, after one side of the ceramic silicone foam sheet is ablated by acetylene plus oxygen flame at 1300°C for 10 minutes, no cracks appear on the other side. In the present invention, by controlling one side of the foam sheet to be ablated by acetylene plus oxygen flame at 1300°C for 10 minutes, no cracks appear on the other side, so that the foam sheet can form a hard and dense ceramic body after high-temperature ablation, which can effectively prevent the flame from burning through when the battery core catches fire, and has a better fireproof effect.

[0055] In some embodiments, the Shore A hardness of the ceramicized silicone foam sheet is 5-15°. From the perspective of making the compression stress-strain curve of the foam sheet smooth, the Shore A hardness of the foam sheet is set within the above range in the present invention, so that the foam sheet has better cushioning performance.

[0056] On the one hand, the ceramicized silicone foam sheet of the present invention has the characteristics of small and appropriate compressive stress and a gentle compressive stress-strain curve, which can provide appropriate pre-tightening force for the battery cell, and can effectively absorb the volume expansion force of the soft-pack battery cell, and has a shock-absorbing effect, has better buffering performance, and can extend the service life of the battery cell; on the other hand, when the battery cell has thermal runaway, the foam sheet of the present invention can quickly form a hard and dense ceramic body with high ceramic strength, which can prevent the spread of flames, effectively block heat transfer, and protect adjacent battery cells from thermal runaway.

[0057] <Raw materials for ceramic silicone foam sheets>

[0058] According to a specific embodiment of the present invention, the ceramic silicone foam sheet of the present invention comprises at least the following raw materials: a silicone rubber matrix, a foaming agent, a ceramic filler, a flux and a heat shrink agent. In parts by weight, the amount of the silicone rubber matrix is ​​100 parts, the amount of the foaming agent is 3 to 30 parts, the amount of the ceramic filler is 40 to 100 parts, the amount of the flux is 5 to 20 parts, and the amount of the heat shrink agent is 1 to 5 parts. Preferably, relative to the amount of the silicone rubber matrix being 100 parts by weight, the raw materials of the ceramic silicone foam sheet further include one or more of the following additives: 5 to 20 parts of reinforcing agent, 10 to 30 parts of flame retardant, 5-15 parts of hydrogenated silicone oil, 0.1 to 3 parts of catalyst, 0.01 to 0.3 parts of inhibitor, and 1 to 5 parts of structural additive. More preferably, the total amount of all ceramic fillers, fluxes, heat shrink agents, optionally contained reinforcing agents and optionally contained flame retardants accounts for 40% to 50% of the total weight of all raw materials of the foam sheet.

[0059] In some embodiments, the silicone rubber matrix includes an organic polysiloxane having at least 2 alkenyl groups. Examples of the alkenyl group include: vinyl, allyl, hexenyl, etc. Among them, vinyl is preferred. In addition, examples of organic groups bonded to silicon atoms other than alkenyl groups include: methyl, phenyl, etc. Specifically, the silicone rubber matrix includes α,ω-divinyl polydimethylsiloxane. Preferably, the viscosity of the silicone rubber matrix at 25°C is 500~500000mP•s. Two or more silicone rubber matrices with different viscosities within this viscosity range can be mixed and used. If the viscosity of the silicone rubber matrix is ​​lower than 500mP•s, the crosslinking degree of the raw material after curing is too large, making the hardness of the foam sheet too large; if the viscosity is higher than 500000mP•s, the viscosity of the raw material is too large, making the processing of the foam sheet such as mixing difficult.

[0060] In some embodiments, the foaming agent includes one or more of hydroxy silicone oil, isopropanol, n-butanol, ethanol and water. Preferably, the foaming agent includes one or more of hydroxy silicone oil, isopropanol and ethanol. The side chain of the hydroxy silicone oil is methyl, and the mass fraction of the hydroxyl group is preferably 1% to 10%. The purity of the isopropanol, n-butanol and ethanol is above 99.5%.

[0061] In some embodiments, the ceramic filler includes one or more of montmorillonite, wollastonite, kaolin, diatomaceous earth, mica, zirconium oxide, aluminum oxide and activated magnesium oxide. Preferably, the ceramic filler includes at least two sizes of wollastonite, namely, a first wollastonite and a second wollastonite, wherein the first wollastonite has an average particle size of 2 to 25 µm and an aspect ratio of 3 to 10, and the second wollastonite has an average particle size of 2 to 25 µm and an aspect ratio of 20 to 40, and the weight ratio of the first wollastonite to the second wollastonite is preferably 4: (1 to 2). If the weight ratio of the first wollastonite to the second wollastonite is greater than 4: 1, the ceramic strength of the foamed sheet is too low; if the weight ratio of the first wollastonite to the second wollastonite is less than 2: 1, it has an adverse effect on the foaming degree of the foamed sheet.

[0062] In some embodiments, the flux includes one or more of zinc borate, borax, and low-melting-point glass powder, etc. Preferably, the flux includes low-melting-point glass powder, the melting temperature of which is 300-800°C.

[0063] In some embodiments, the heat shrink agent includes a thermoplastic resin. Specifically, the thermoplastic resin includes one or more of high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), ethylene-vinyl acetate copolymer (EVA), ethylene-ethyl acrylate copolymer (EEA), ethylene propylene diene monomer (EPDM), polycarbonate (PC) and polyethylene terephthalate (PET). In addition, the thermoplastic resin is in powder form, and the average particle size of the thermoplastic resin powder is preferably ≤50μm. If the average particle size of the thermoplastic resin powder is greater than 50μm, the raw material will have a granular feel, and the appearance of the foam sheet will be poor and the three-point bending strength will be too low, and the heat insulation and fire prevention will be poor. Preferably, the thermoplastic resin includes one or more of ethylene-vinyl acetate copolymer (EVA), ethylene-ethyl acrylate copolymer (EEA) and ethylene propylene diene monomer (EPDM); more preferably, the mass content of the structural unit derived from vinyl acetate in the ethylene-vinyl acetate copolymer (EVA) is 20% to 40%, and the mass content of the structural unit derived from ethyl acrylate in the ethylene-ethyl acrylate copolymer (EEA) is 10% to 30%. If the mass content of the structural unit derived from vinyl acetate in EVA or the mass content of the structural unit derived from ethyl acrylate in EEA is lower than the above range, the hardness and rigidity of the thermoplastic resin powder are too large, thereby causing the compressive stress of the foam sheet to be too large; if the mass content of the structural unit derived from vinyl acetate in EVA or the mass content of the structural unit derived from ethyl acrylate in EEA is higher than the above range, the thermoplastic resin powder is too soft, thereby causing the compressive stress of the foam sheet to be too small, and at the same time, under the strong shearing action during the mixing of the raw materials, the thermoplastic resin powder is easily broken, causing the viscosity of the raw materials to be too large, affecting the processing of the foam sheet. The present invention controls the amount of the heat shrink agent to be 1-5 parts (relative to 100 parts by weight of the silicone rubber substrate); if the amount of the heat shrink agent is less than 1 part, its heat shrinkage effect cannot be fully exerted; if the amount of the heat shrink agent is more than 5 parts, the porcelain strength of the foam sheet will be too low and the fireproof performance will be poor.

[0064] The present invention adopts a thermoplastic resin as a heat shrink agent. When the foam sheet expands due to heat, the thermoplastic resin shrinks due to heat, which can inhibit the thermal deformation of the foam sheet, thereby reducing the thermal cracking of the foam sheet, maintaining the integrity of the foam sheet, and making the foam sheet have better thermal insulation and fireproof performance at high temperatures. It can well isolate flames and slow down the heat transfer rate when thermal runaway occurs in the battery core.

[0065] In some embodiments, the reinforcing agent comprises nano-silicon dioxide. The specific surface area of ​​the nano-silicon dioxide is preferably 100-400 m 2 / g. More preferably, the nano silicon dioxide is fumed silica.

[0066] In some embodiments, the flame retardant includes one or more of aluminum hydroxide, magnesium hydroxide, zinc borate, antimony oxide, and molybdenum compounds. Preferably, the flame retardant includes one or more of aluminum hydroxide and zinc borate. The average particle size of the flame retardant is preferably 1-10 μm.

[0067] In some embodiments, the hydrogen-containing silicone oil contains at least three silicon-hydrogen bonds on one molecule, and the hydrogen-containing silicone oil commonly used in the art can be used, such as but not limited to one or more of terminal hydrogen polysiloxane, side hydrogen polysiloxane, terminal hydrogen side hydrogen polysiloxane, etc. Preferably, the hydrogen content of the hydrogen-containing silicone oil is 0.8%~1.6% (mass content), and the molecular weight is 400~3000g / mol. If the hydrogen content of the hydrogen-containing silicone oil is lower than or higher than the above range, it cannot be foamed into a foam sheet with a density and hardness within the range of the present invention; if the molecular weight of the hydrogen-containing silicone oil is lower than the above range, it is easy to volatilize, and the hydrogen-containing silicone oil in the raw material before vulcanization will be lost; if the molecular weight of the hydrogen-containing silicone oil is higher than the above range, the molecular chain of the hydrogen-containing silicone oil is prone to steric hindrance, and some silicon-hydrogen bonds cannot participate in the reaction, so that the foaming ratio of the foam sheet is too low.

[0068] In some embodiments, the catalyst includes one or more of a platinum catalyst, a palladium catalyst, and a rhodium catalyst. Among them, the platinum catalyst has a better effect, and the platinum content of the platinum catalyst can be 1000ppm, 3000ppm, or 5000ppm. Specifically, the platinum catalyst includes: chloroplatinic acid, a coordination compound of chloroplatinic acid and an olefin, a vinyl siloxane or an acetylene compound, an alcohol-modified chloroplatinic acid, and a coordination compound of platinum and an olefin, a vinyl siloxane or an acetylene compound. One or more of the above. Preferably, the catalyst includes a chloroplatinic acid tetramethyl divinyl disiloxane complex, and its platinum content is preferably 5000ppm.

[0069] In some embodiments, the inhibitor includes one or more of diethyl fumarate, 2-methyl-3-butyn-2-ol, 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-phenyl-1-butyn-3-ol, 1-hexynyl-1-cyclohexanol and tetravinylcyclotetrasiloxane, etc. Preferably, the inhibitor includes one or more of 3-methyl-1-butyn-3-ol and 1-hexynyl-1-cyclohexanol.

[0070] In some embodiments, the structural aid includes one or more of dimethylvinylethoxysilane, methylvinyldimethoxysilane and methylvinyldiethoxysilane. The present invention adopts the structural aid to reduce the crosslinking degree of the foam sheet, increase the softness of the foam sheet and make its compressive stress lower. If the amount of the structural aid is less than 1 part, the effect is not obvious; if the amount of the structural aid is greater than 5 parts, the compressive stress of the foam sheet will be too low.

[0071] <Method for preparing ceramic silicone foam sheet>

[0072] The preparation method of the ceramic silicone foam sheet of the present invention may include the steps of mixing the raw materials of the foam sheet, calendering, and vulcanization.

[0073] In some embodiments, the method for preparing the ceramic silicone foam sheet of the present invention may include the following steps:

[0074] (1) mixing a portion of a silicone rubber matrix, a foaming agent, a portion of a ceramic filler and a selectively added catalyst to obtain a rubber material A;

[0075] (2) mixing another portion of the silicone rubber matrix, another portion of the ceramic filler, a solvent, a heat shrink agent, an optionally added reinforcing agent, an optionally added flame retardant, an optionally added hydrogenated silicone oil, an optionally added inhibitor, and an optionally added structural additive to obtain a rubber material B;

[0076] (3) After mixing the rubber material A and the rubber material B, coating them on a release film, and then calendering to obtain a molded product;

[0077] (4) vulcanizing the molded product to obtain the ceramicized silicone foam sheet.

[0078] In some embodiments, the mixing of steps (1) and (2) above can be carried out in a planetary stirred tank, respectively, and the mixing conditions can include: temperature of 10-50°C, revolution speed of 100-200 r / min, rotation speed of 300-500 r / min, pressure of -0.09-0.1 MPa, and mixing time of 2-4 h.

[0079] In some embodiments, the mixing ratio of rubber material A and rubber material B can be conventionally adjusted by a person skilled in the art, for example, the weight ratio can be 1:1, and the ratio of the two parts of the silicone rubber matrix and the ratio of the two parts of the ceramic filler in steps (1) and (2) can also be conventionally adjusted by a person skilled in the art.

[0080] In some embodiments, the release film may be a conventional release film, such as a PET release film.

[0081] In some embodiments, the vulcanization includes primary vulcanization and secondary vulcanization; the temperature of the primary vulcanization is 40-100°C and the time is 5-10 minutes; the temperature of the secondary vulcanization is 140-180°C and the time is 30-40 minutes. The release film can be peeled off after the primary vulcanization is completed, and then the secondary vulcanization is performed. It can be understood by those skilled in the art that foaming is achieved during the vulcanization process, and cross-linking may also be performed during the vulcanization process.

[0082] <Application of ceramic silicone foam sheet>

[0083] The application fields of the ceramic silicone foam sheet provided by the present invention may include various buffer insulation materials, thermal runaway protection materials, insulation materials, etc., for example but not limited to applications in batteries.

[0084] Specifically, the ceramic silicone foam sheet of the present invention can be used between soft-pack battery cells in a battery module.

[0085] According to a specific embodiment of the present invention, the present invention provides a battery module, which includes: more than two soft-pack battery cells and more than one ceramic silicone foam sheet, wherein the ceramic silicone foam sheet is arranged between adjacent soft-pack battery cells.

[0086] According to a specific embodiment of the present invention, the present invention also provides a battery pack, which includes: a box body and a battery module; the box body includes a module frame, a module cover, a wiring harness isolation plate and a liquid cooling plate; the battery module includes two or more soft-pack battery cells and one or more ceramic silicone foam sheets, and the ceramic silicone foam sheets are arranged between adjacent soft-pack battery cells; the battery module is arranged in the module frame, the module cover is arranged on the top of the battery module, the wiring harness isolation plate is arranged between the battery module and the module cover, the wiring harness isolation plate is provided with a bus for connecting the soft-pack battery cells, and the liquid cooling plate is arranged around the battery module.

[0087] In some embodiments, the battery module assembled with the ceramic silicone foam sheet having a thickness of 2±0.2 mm has a capacity retention rate of ≥90% after 500 charge and discharge cycles. The battery module has a high capacity retention rate and thus a long service life.

[0088] The ceramicized silicone foam sheet of the present invention has both high ceramic strength, small and appropriate compression stress, and a gentle compression stress-strain curve. It is suitable for use in battery modules and battery packs as a buffer, heat-insulating and fire-proof gasket between soft-pack batteries to effectively protect the batteries. The foam sheet of the present invention is arranged between the soft-pack batteries. During the charge and discharge process of the batteries, the force between the foam sheet of the present invention and the batteries is gentle, which can effectively absorb the volume expansion force of the soft-pack batteries, and there will be no slippage between the foam sheet and the batteries. At the same time, the foam sheet will not cause serious extrusion between the layers inside the batteries, and the foam sheet of the present invention also has shock-absorbing performance. Therefore, the foam sheet of the present invention has better buffering performance, so that the battery module using the foam sheet has a capacity retention rate of ≥90% after 500 charge and discharge cycles, which prolongs the service life of the batteries. In addition, the foam sheet of the present invention is arranged between soft-pack battery cells to also play a role of heat insulation and fire prevention. The foam sheet can quickly form a hard and dense ceramic body when the battery cell has thermal runaway. It has a high ceramic strength, can prevent the spread of flames, slow down heat transfer, and protect adjacent battery cells from thermal runaway.

[0089] <Test Method>

[0090] 1. Foaming ratio:

[0091] Take an appropriate amount of the surface of the ceramic silicone foam sheet sample and test the density of the surface according to method A in GB / T 533-2008. , g / cm 3 ; The density of the ceramic silicone foam sheet sample is tested according to the method in GB / T 6343-2009 (the apparent total density of the foam sheet sample (including the skin) calculated by formula (1) in 7.1 is ρ1), g / cm 3 ; Calculate the expansion ratio R of the ceramic silicone foam sheet sample according to the following formula:

[0092] R=ρ s / ρ1

[0093] The epidermis of the ceramic silicone foam sheet sample is the part located on the surface of the sample without pores. Those skilled in the art can distinguish the epidermis by naked eye observation or microscope observation. The area of ​​the epidermis can be ≥100mm 2 .

[0094] 2. NMR transverse relaxation time T2:

[0095] The NMR-nuclear magnetic resonance spectrometer (the instrument used in the specific embodiments and comparative examples below is the FPMAG-Kea2-NMR-nuclear magnetic resonance spectrometer) was used to test the nuclear magnetic resonance transverse relaxation time T2 of the ceramicized silicone foam sheet sample. The test conditions include: using CPMG pulse sequence excitation, the sensor frequency is 6.0 MHz, the pulse width D=4.5 μs, the echo time TE=120 μs, the number of 180° pulses is 1000, the repetition time is 1000 ms, the 90° pulse amplitude is -20 dB, and the 180° pulse amplitude is -14 dB.

[0096] 3. Opening rate:

[0097] Test the vacuum volume water absorption rate θ of the ceramic silicone foam sheet sample according to the method in Appendix B of GB / T 17794-2021; take a new ceramic silicone foam sheet sample, take an appropriate amount of the sample's surface, and test the surface density ρ according to method A in GB / T 533-2008 s , g / cm 3 ; The density of the ceramic silicone foam sheet sample is tested according to the method in GB / T 6343-2009 (the apparent total density of the foam sheet sample (including the skin) calculated by formula (1) in 7.1 is ρ1), g / cm 3 ; Calculate the open porosity χ of the ceramic silicone foam sheet sample according to the following formula:

[0098]

[0099] The epidermis of the ceramic silicone foam sheet sample is the part located on the surface of the sample without pores. Those skilled in the art can distinguish the epidermis by naked eye observation or microscope observation. The area of ​​the epidermis can be ≥100mm 2 .

[0100] 4. Thermal weight loss:

[0101] Take the ceramic silicone foam sheet sample and weigh it, and the weight is recorded as m0; then, heat the muffle furnace to 800℃, and then place the weighed sample in the muffle furnace. After ablation at 800℃ for 30min, take out the sample and weigh it, and the weight is recorded as m1; calculate the thermal weight loss of the ceramic silicone foam sheet sample according to the following formula:

[0102] Thermal weight loss = (m0-m1) / m0×100%.

[0103] 5. Three-point bending strength:

[0104] Take a ceramic silicone foam sheet sample (for example, the plane size is (80±0.5) mm×(10±0.5) mm) and place it in a muffle furnace preheated to 800°C. After ablation for 30 minutes, take out the sample and cool it to room temperature. Then test the three-point bending strength of the sample according to the method in GB / T1449-2005. The test speed is 5 mm / min. The bending strength of the sample calculated by formula (1) in 9.1 of GB / T1449-2005 is the three-point bending strength of the ceramic silicone foam sheet sample after ablation at 800°C for 30 minutes.

[0105] 6. Density:

[0106] The density of the ceramic silicone foam sheet sample is tested according to the method in GB / T 6343-2009 (the apparent total density of the foam sheet sample (including the skin) is calculated using formula (1) in 7.1).

[0107] 7. Ratio of 10% compressive stress and 70% compressive stress to 10% compressive stress:

[0108] According to the method in GB / T 18942.1-2003, the 10% compressive stress and 70% compressive stress of the ceramic silicone foam sheet sample (for example, the plane size is (50±0.5) mm×(50±0.5) mm) are tested, and the ratio of the 70% compressive stress to the 10% compressive stress is calculated. Specifically, the thickness of the sample to be tested is 10 mm or more (for the foam sheet sample with a thickness of less than 10 mm, multiple foam sheet samples should be stacked to a thickness of more than 10 mm); before the test, a prestress of (100±10) Pa is applied to the sample, and after the prestress load is completed, the display value of the compression rate of the testing machine is adjusted to zero; the sample is compressed at a rate of (50±10)% of its initial thickness per minute; the compressive stress of the sample when the first compression is compressed to a compression rate of 10% (i.e., compressed to 90% of the initial thickness of the sample) and the first compression is compressed to a compression rate of 70% (i.e., compressed to 30% of the initial thickness of the sample) is tested.

[0109] 8. Thickness:

[0110] Take at least 3 ceramic silicone foam sheet samples (plane size, for example, (5±0.5) mm×(5±0.5) mm) and place them in an environment with a temperature of 23~27°C and a humidity of 45~55% for 2 hours. Then measure the thickness of each sample with a vernier caliper, and take the average value to obtain the thickness of the ceramic silicone foam sheet sample.

[0111] 9. Average cell diameter:

[0112] Randomly select several locations (e.g., 5) on the ceramic silicone foam sheet sample, and cut several (e.g., 3) square samples with a side length of 10±1 mm at each location. Use a digital microscope to take magnified photos of the 4 cut surfaces of each sample. On each cut surface, randomly select a 2mm×2mm area, and measure the diameter of all the cells in the area in the direction perpendicular to the upper and lower sides of the sample. Calculate the average value of all the measured cell diameters as the average cell diameter of the ceramic silicone foam sheet sample.

[0113] 10. Temperature and insulation coefficient of the other side when one side is heated:

[0114] Take a ceramic silicone foam sheet sample with a plane size of (120±2) mm×(120±2) mm. Use a thermal insulation performance tester (the equipment used in the specific examples and comparative examples below is an RBC-II-30KN thermal insulation material thermal insulation performance tester) to test the temperature of one side and the temperature of the other side of the sample when it is heated at 800°C for 5 minutes, and calculate the thermal insulation coefficient of the ceramic silicone foam sheet sample according to the following formula:

[0115] Thermal insulation coefficient = (temperature of one side of the ceramic silicone foam sheet sample when heated at 800°C for 5 minutes - temperature of the other side of the sample) ÷ thickness of the sample.

[0116] Repeat the above test and calculation process at least 5 times and take the average value.

[0117] 11. 1300℃ acetylene oxygen flame ablation test:

[0118] Take a ceramic silicone foam sheet sample (for example, the plane size is (120±2) mm×(120±2) mm) and place it on a horizontal metal ring. Use a flame spray gun (the flame spray gun used in the specific embodiments and comparative examples below is a liquefied gas flame spray gun 30-1), adjust the temperature of the acetylene oxygen flame to 1300°C, the flame length is 8-10 cm, and make one end of the acetylene oxygen flame contact one side of the sample, and ablate for 10 minutes. Then observe whether cracks appear on the other side of the sample. Those skilled in the art can judge whether cracks appear on the other side of the sample by naked eye observation.

[0119] 12. Shore A hardness:

[0120] According to the test method of A-type Shore hardness tester in GB / T 531.1-2008, the hardness A of the ceramicized silicone foam sheet sample was tested.

[0121] 13. Battery module charge and discharge cycle test:

[0122] The battery modules used for testing include: Figure 1As shown, two soft-pack battery cells 1 (length is (150±10) mm, width is (100±10) mm, thickness is (40±10) mm) arranged in parallel; a clamping plate 2 is respectively arranged on both sides of the two soft-pack battery cells in the thickness direction of the soft-pack battery cells; a foam sheet sample 3 (the length and width of the foam sheet sample 3 are respectively the length and width of the soft-pack battery cell 1 ±2 mm, and the thickness is (2±0.2) mm) is arranged between the two soft-pack battery cells 1 and between the soft-pack battery cell 1 and the clamping plate 2; a pressure sensor 4 for testing the force between the foam sheet sample 3 and the soft-pack battery cell 1; and a fastener 5 (such as a screw and a nut, etc.) for fixing the clamping plate 2 and the soft-pack battery cell 1.

[0123] It should be noted that the foam sheet sample 3 is the ceramic silicone foam sheet of the present invention, and the desired thickness can be obtained by cross-sectioning in a direction perpendicular to its thickness direction, or by stacking multiple foam sheet samples 3 in the thickness direction to obtain the desired thickness.

[0124] The test steps include: adjusting the preload force between the foam sheet sample 3 and the soft-pack battery cell 1 by adjusting the distance between the two clamping plates 2, adjusting the initial preload force to 0.1MPa, and then testing the capacity retention rate of the battery module after 500 charge and discharge cycles in accordance with the operating cycle life test method (6.5.3) of energy-type batteries for pure electric passenger vehicles in GB / T31484-2015. Example

[0125] The technical solutions of the present invention are specifically described below by way of examples, but the present invention is not limited to these examples and can of course be implemented in various modifications within the scope of the gist of the present invention.

[0126] Example 1

[0127] (1) In parts by weight, 50 parts of silicone rubber matrix, 20 parts of foaming agent, 56.93 parts of ceramic filler and 1.2 parts of catalyst were added into a planetary stirring kettle for mixing to obtain rubber material A; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0128] (2) In parts by weight, 50 parts of silicone rubber matrix, 23.07 parts of ceramic filler, 10 parts of flux, 2 parts of heat shrink agent, 15 parts of reinforcing agent, 15 parts of flame retardant, 12 parts of hydrogenated silicone oil, 0.06 parts of inhibitor and 1 part of structural additive were added into a planetary stirring kettle for mixing to obtain rubber material B; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0129] (3) mixing the rubber material A and the rubber material B in a weight ratio of 1:1 by a feeder, coating the mixture on a PET release film, and then calendering the mixture by a calender to obtain a molded product;

[0130] (4) The molded product is subjected to a primary vulcanization in a vulcanization oven at 70°C for 10 minutes, the PET release film is peeled off, and then a secondary vulcanization is carried out in a vulcanization oven at 150°C for 40 minutes to obtain a ceramicized silicone foam sheet.

[0131] Among them, the silicone rubber matrix is ​​A1, the foaming agent is H1, the ceramic filler is a combination of B1, B2 and B3, the catalyst is I, the flux is E, the heat shrink agent is F2, the reinforcing agent is C, the flame retardant is D1, the hydrogen-containing silicone oil is G2, the inhibitor is J, and the structural additive is K1. For the specific description of these raw materials, please see Table 1 below.

[0132] Example 2

[0133] (1) In parts by weight, 50 parts of silicone rubber matrix, 20 parts of foaming agent, 54.93 parts of ceramic filler and 1.2 parts of catalyst were added into a planetary stirring kettle for mixing to obtain rubber material A; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0134] (2) In parts by weight, 50 parts of silicone rubber matrix, 25.07 parts of ceramic filler, 15 parts of flux, 2 parts of heat shrink agent, 10 parts of reinforcing agent, 10 parts of flame retardant, 12 parts of hydrogenated silicone oil, 0.06 parts of inhibitor and 2 parts of structural additive were added into a planetary stirring kettle for mixing to obtain rubber material B; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0135] (3) mixing the rubber material A and the rubber material B in a weight ratio of 1:1 by a feeder, coating the mixture on a PET release film, and then calendering the mixture by a calender to obtain a molded product;

[0136] (4) The molded product is subjected to a primary vulcanization in a vulcanization oven at 70°C for 10 minutes, the PET release film is peeled off, and then a secondary vulcanization is carried out in a vulcanization oven at 150°C for 40 minutes to obtain a ceramicized silicone foam sheet.

[0137] Among them, the silicone rubber matrix is ​​A3, the foaming agent is H1, the ceramic filler is a combination of B1, B2 and B4, the catalyst is I, the flux is E, the heat shrink agent is F7, the reinforcing agent is C, the flame retardant is a combination of D1 and D2, the hydrogen-containing silicone oil is G2, the inhibitor is J, and the structural additive is K1. For the specific description of these raw materials, please see Table 1 below.

[0138] Example 3

[0139] (1) In parts by weight, 50 parts of silicone rubber matrix, 28 parts of foaming agent, 43.43 parts of ceramic filler and 1.2 parts of catalyst were added into a planetary stirring kettle for mixing to obtain rubber material A; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0140] (2) In parts by weight, 50 parts of silicone rubber matrix, 11.57 parts of ceramic filler, 10 parts of flux, 2 parts of heat shrink agent, 10 parts of reinforcing agent, 20 parts of flame retardant, 15 parts of hydrogenated silicone oil, 0.06 parts of inhibitor and 4 parts of structural additive were added into a planetary stirring kettle for mixing to obtain rubber material B; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0141] (3) mixing the rubber material A and the rubber material B in a weight ratio of 1:1 by a feeder, coating the mixture on a PET release film, and then calendering the mixture by a calender to obtain a molded product;

[0142] (4) The molded product is subjected to a primary vulcanization in a vulcanization oven at 70°C for 10 minutes, the PET release film is peeled off, and then a secondary vulcanization is carried out in a vulcanization oven at 140°C for 40 minutes to obtain a ceramicized silicone foam sheet.

[0143] Among them, the silicone rubber matrix is ​​A2, the foaming agent is H1, the ceramic filler is a combination of B1, B2 and B3, the catalyst is I, the flux is E, the heat shrink agent is F4, the reinforcing agent is C, the flame retardant is D2, the hydrogen-containing silicone oil is G3, the inhibitor is J, and the structural additive is K2. For the specific description of these raw materials, please see Table 1 below.

[0144] Example 4

[0145] (1) In parts by weight, 50 parts of silicone rubber matrix, 20 parts of foaming agent, 57.43 parts of ceramic filler and 1.2 parts of catalyst were added into a planetary stirring kettle for mixing to obtain rubber material A; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0146] (2) In parts by weight, 50 parts of silicone rubber matrix, 42.57 parts of ceramic filler, 10 parts of flux, 2 parts of heat shrink agent, 5 parts of reinforcing agent, 10 parts of flame retardant, 8 parts of hydrogenated silicone oil, 0.06 parts of inhibitor and 1 part of structural additive were added into a planetary stirring kettle for mixing to obtain rubber material B; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0147] (3) mixing the rubber material A and the rubber material B in a weight ratio of 1:1 by a feeder, coating the mixture on a PET release film, and then calendering the mixture by a calender to obtain a molded product;

[0148] (4) The molded product is subjected to a primary vulcanization in a vulcanization oven at 70°C for 10 minutes, the PET release film is peeled off, and then a secondary vulcanization is carried out in a vulcanization oven at 150°C for 40 minutes to obtain a ceramicized silicone foam sheet.

[0149] Among them, the silicone rubber matrix is ​​a combination of A2 and A3, the foaming agent is H1, the ceramic filler is a combination of B1 and B2, the catalyst is I, the flux is E, the heat shrink agent is F11, the reinforcing agent is C, the flame retardant is D1, the hydrogen-containing silicone oil is G1, the inhibitor is J, and the structural additive is K3. For the specific description of these raw materials, please see Table 1 below.

[0150] Example 5

[0151] (1) In parts by weight, 50 parts of silicone rubber matrix, 20 parts of foaming agent, 48.93 parts of ceramic filler and 1.2 parts of catalyst were added into a planetary stirring kettle for mixing to obtain rubber material A; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0152] (2) In parts by weight, 50 parts of silicone rubber matrix, 21.07 parts of ceramic filler, 5 parts of flux, 4 parts of heat shrink agent, 10 parts of reinforcing agent, 20 parts of flame retardant, 8 parts of hydrogenated silicone oil, 0.06 parts of inhibitor and 2 parts of structural additive were added into a planetary stirring kettle for mixing to obtain rubber material B; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0153] (3) mixing the rubber material A and the rubber material B in a weight ratio of 1:1 by a feeder, coating the mixture on a PET release film, and then calendering the mixture by a calender to obtain a molded product;

[0154] (4) The molded product is subjected to a primary vulcanization in a vulcanization oven at 70°C for 10 minutes, the PET release film is peeled off, and then a secondary vulcanization is carried out in a vulcanization oven at 150°C for 40 minutes to obtain a ceramicized silicone foam sheet.

[0155] Among them, the silicone rubber matrix is ​​a combination of A1 and A2, the foaming agent is H1, the ceramic filler is a combination of B1, B2 and B4, the catalyst is I, the flux is E, the heat shrink agent is a combination of F3 and F11, the reinforcing agent is C, the flame retardant is D1, the hydrogen-containing silicone oil is G1, the inhibitor is J, and the structural additive is K1. For the specific description of these raw materials, please see Table 1 below.

[0156] Example 6

[0157] (1) In parts by weight, 50 parts of silicone rubber matrix, 5 parts of foaming agent, 55.92 parts of ceramic filler and 1.2 parts of catalyst were added into a planetary stirring kettle for mixing to obtain rubber material A; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0158] (2) In parts by weight, 50 parts of silicone rubber matrix, 4.08 parts of ceramic filler, 10 parts of flux, 2 parts of heat shrink agent, 5 parts of reinforcing agent, 25 parts of flame retardant, 12 parts of hydrogenated silicone oil, 0.04 parts of inhibitor and 4 parts of structural additive were added into a planetary stirring kettle for mixing to obtain rubber material B; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0159] (3) mixing the rubber material A and the rubber material B in a weight ratio of 1:1 by a feeder, coating the mixture on a PET release film, and then calendering the mixture by a calender to obtain a molded product;

[0160] (4) The molded product is subjected to a primary vulcanization in a vulcanization oven at 70°C for 10 minutes, the PET release film is peeled off, and then a secondary vulcanization is carried out in a vulcanization oven at 150°C for 40 minutes to obtain a ceramicized silicone foam sheet.

[0161] Among them, the silicone rubber matrix is ​​A1, the foaming agent is H2, the ceramic filler is a combination of B1, B2 and B3, the catalyst is I, the flux is E, the heat shrink agent is F9, the reinforcing agent is C, the flame retardant is a combination of D1 and D2, the hydrogen-containing silicone oil is G2, the inhibitor is J, and the structural additive is K3. For the specific description of these raw materials, please see Table 1 below.

[0162] Example 7

[0163] (1) In parts by weight, 50 parts of silicone rubber matrix, 5 parts of foaming agent, 62.42 parts of ceramic filler and 1.2 parts of catalyst were added into a planetary stirring kettle for mixing to obtain rubber material A; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0164] (2) In parts by weight, 50 parts of silicone rubber matrix, 17.58 parts of ceramic filler, 10 parts of flux, 2 parts of heat shrink agent, 5 parts of reinforcing agent, 15 parts of flame retardant, 15 parts of hydrogenated silicone oil, 0.04 parts of inhibitor and 4 parts of structural additive were added into a planetary stirring kettle for mixing to obtain rubber material B; the mixing conditions included: temperature of 23-28°C, revolution speed of 150 r / min, rotation speed of 400 r / min, pressure of -0.09-0.1 MPa, and mixing time of 3 h;

[0165] (3) mixing the rubber material A and the rubber material B in a weight ratio of 1:1 by a feeder, coating the mixture on a PET release film, and then calendering the mixture by a calender to obtain a molded product;

[0166] (4) The molded product is subjected to a primary vulcanization in a vulcanization oven at 70°C for 10 minutes, the PET release film is peeled off, and then a secondary vulcanization is carried out in a vulcanization oven at 150°C for 40 minutes to obtain a ceramicized silicone foam sheet.

[0167] Among them, the silicone rubber matrix is ​​a combination of A2 and A3, the foaming agent is H3, the ceramic filler is a combination of B1, B2 and B3, the catalyst is I, the flux is E, the heat shrink agent is F8, the reinforcing agent is C, the flame retardant is D1, the hydrogen-containing silicone oil is G3, the inhibitor is J, and the structural additive is K2. For the specific description of these raw materials, please see Table 1 below.

[0168] Comparative Examples 1 to 8

[0169] Comparative Examples 1 to 8 respectively provide ceramic silicone foam sheets, and the preparation steps of these foam sheets are the same as those of Example 1, except that the raw materials of these foam sheets are different from those of Example 1. It should be noted that the mixing weight ratio of rubber material A and rubber material B in the preparation steps of Comparative Examples 1 to 8 is 1:1, and the amount of the silicone rubber matrix in rubber material A and rubber material B is 50 parts by weight, based on which the weight parts of the ceramic fillers in rubber material A and rubber material B can be calculated.

[0170] The raw material compositions of the ceramic silicone foam sheets of Comparative Examples 1 to 8 are shown in Table 2.

[0171] Table 1 Raw material composition of ceramic silicone foam sheets of Examples 1 to 7 (parts by weight)

[0172]

[0173] Table 2 Raw material composition of ceramic silicone foam sheets of comparative examples 1 to 8 (parts by weight)

[0174]

[0175] Description of the raw materials in Table 1 and Table 2:

[0176] The raw materials used in the examples and comparative examples of the present invention are all commercially available products:

[0177] A1: Vinyl silicone oil, viscosity 20000mP•s at 25℃;

[0178] A2: Vinyl silicone oil, viscosity 80000mP•s at 25°C;

[0179] A3: Vinyl silicone oil, viscosity 2000mP•s at 25°C;

[0180] A4: Vinyl silicone oil, viscosity 200mP•s at 25°C;

[0181] The structural formulas of A1~A4 are: ;

[0182] B1: wollastonite, average particle size 5µm, aspect ratio 5;

[0183] B2: wollastonite, average particle size 8µm, aspect ratio 35;

[0184] B3: mica powder, average particle size 7µm, aspect ratio 20;

[0185] B4: kaolin, average particle size 325 mesh;

[0186] C: Fumed white carbon black (i.e., fumed nano-silica), the specific surface area measured by the BET method is 200m 2 / g;

[0187] D1: aluminum hydroxide, average particle size 5.5µm;

[0188] D2: zinc borate, average particle size 4µm;

[0189] E: low melting point glass powder, average particle size 4µm, is a mixed powder obtained by mixing two low melting point glass powders with melting temperatures of 430°C and 750°C in a weight ratio of 1:1;

[0190] F1: ethylene-vinyl acetate copolymer (EVA), VA mass content 15%, average particle size 35 μm;

[0191] F2: ethylene-vinyl acetate copolymer (EVA), VA mass content 20%, average particle size 35 μm;

[0192] F3: ethylene-vinyl acetate copolymer (EVA), VA mass content 30%, average particle size 45 μm;

[0193] F4: ethylene-vinyl acetate copolymer (EVA), VA mass content 40%, average particle size 35 μm;

[0194] F5: ethylene-vinyl acetate copolymer (EVA), VA mass content 45%, average particle size 15 μm;

[0195] F6: ethylene-ethyl acrylate copolymer (EEA), EA content 5%, average particle size 35 μm;

[0196] F7: ethylene-ethyl acrylate copolymer (EEA), EA content 10%, average particle size 35 μm;

[0197] F8: ethylene-ethyl acrylate copolymer (EEA), EA content 20%, average particle size 35 μm;

[0198] F9: ethylene-ethyl acrylate copolymer (EEA), EA content 30%, average particle size 35 μm;

[0199] F10: ethylene-ethyl acrylate copolymer (EEA), EA content 35%, average particle size 35 μm;

[0200] F11: EPDM, average particle size 45 μm;

[0201] F12: ethylene-vinyl acetate copolymer (EVA), VA mass content 30%, average particle size 55 μm;

[0202] G1: Hydrogenated silicone oil, hydrogen content 1.6% (mass content), molecular weight 400g / mol;

[0203] G2: Hydrogenated silicone oil, hydrogen content 1.2% (mass content), molecular weight 3000g / mol;

[0204] G3: Hydrogenated silicone oil, hydrogen content 0.8% (mass content), molecular weight 1500g / mol;

[0205] G4: Hydrogenated silicone oil, hydrogen content 1.8% (mass content), molecular weight 400g / mol;

[0206] G5: Hydrogenated silicone oil, hydrogen content 0.75% (mass content), molecular weight 1600g / mol;

[0207] H1: Hydroxy silicone oil, hydroxyl mass content 5%;

[0208] H2: isopropanol, purity ≥99.7%;

[0209] H3: ethanol, purity ≥99.5%;

[0210] I: Custer platinum catalyst, platinum content 5000ppm;

[0211] J: 1-hexynyl-1-cyclohexanol, purity ≥ 98%;

[0212] K1: dimethylvinylethoxysilane, purity ≥98%;

[0213] K2: methylvinyldimethoxysilane, purity ≥98%;

[0214] K3: Methylvinyldiethoxysilane, purity ≥98%.

[0215] Various parameters of the ceramic silicone foam sheets of Examples 1 to 7 and Comparative Examples 1 to 8 and the charge-discharge cycle test results of the assembled battery modules are shown in Tables 3 and 4, respectively.

[0216] Table 3 Parameters of ceramic silicone foam sheets of Examples 1 to 7 and charge and discharge cycle test results of assembled battery modules

[0217]

[0218] Table 4 Parameters of ceramic silicone foam sheets of Comparative Examples 1 to 8 and charge and discharge cycle test results of assembled battery modules

[0219]

[0220] It can be seen from the above data that one or more of the parameters of the ceramic silicone foam sheets provided in Comparative Examples 1 to 8 are not within the scope of the present invention. These ceramic silicone foam sheets cannot have both high ceramic strength and a smooth compressive stress-strain curve. They either have poor fireproof or heat insulation effects, or poor buffering performance.

[0221] The ceramic silicone foam sheet provided in Examples 1 to 7 of the present invention has, on the one hand, a small and appropriate compressive stress and a flat compressive stress-strain curve, which can provide a suitable preload force for the soft-pack battery cell, and can effectively absorb the volume expansion force of the soft-pack battery cell, and has a shock-absorbing effect, has better buffering performance, and can extend the service life of the battery cell; on the other hand, when the battery cell has thermal runaway, the foam sheet of the present invention can quickly form a hard and dense ceramic body with a high ceramic strength, which can prevent the spread of flames, effectively block heat transfer, and protect adjacent battery cells from thermal runaway.

Claims

1. A battery module, comprising: Two or more soft-pack battery cells and one or more ceramic silicone foam sheets, wherein the ceramic silicone foam sheets are arranged between adjacent soft-pack battery cells; wherein the ceramic silicone foam sheet has a foaming ratio of 3.6 to 6, a nuclear magnetic resonance transverse relaxation time T2 of 105 to 130 ms, an open porosity of ≥20%, and a thermal weight loss of 30 to 50% after ablation at 800°C for 30 minutes; The test conditions of the nuclear magnetic resonance transverse relaxation time T2 include: using CPMG pulse sequence excitation, the sensor frequency is 6.0 MHz, the pulse width D=4.5 μs, the echo time TE=120 μs, the number of 180° pulses is 1000, the repetition time is 1000 ms, the 90° pulse amplitude is -20 dB, and the 180° pulse amplitude is -14 dB; The open porosity is calculated using the following formula: , Wherein, χ is the open porosity of the ceramic silicone foam sheet, and the unit of χ is %; θ is the vacuum volume water absorption of the ceramic silicone foam sheet tested according to the method in Appendix B of GB / T 17794-2021; ρ1 is the density of the ceramic silicone foam sheet tested according to the method in GB / T 6343-2009, and the unit of ρ1 is g / cm 3 ρ s is the density of the surface of the ceramic silicone foam sheet tested according to method A in GB / T 533-2008, ρ s The unit is g / cm 3 .

2. A battery pack comprising: Box and battery module; the box includes a module frame, a module cover, a harness isolation plate and a liquid cooling plate; the battery module includes more than two soft-pack batteries and more than one ceramic silicone foam sheet, and the ceramic silicone foam sheet is arranged between adjacent soft-pack batteries; the battery module is arranged in the module frame, the module cover is arranged on the top of the battery module, the harness isolation plate is arranged between the battery module and the module cover, the harness isolation plate is provided with a busbar for connecting the soft-pack batteries, and the liquid cooling plate is arranged around the battery module; wherein the ceramic silicone foam sheet has a foaming ratio of 3.6-6, a nuclear magnetic resonance transverse relaxation time T2 of 105-130ms, an open porosity of ≥20%, and a thermal weight loss of 30-50% after ablation at 800°C for 30min; The test conditions of the nuclear magnetic resonance transverse relaxation time T2 include: using CPMG pulse sequence excitation, the sensor frequency is 6.0 MHz, the pulse width D=4.5 μs, the echo time TE=120 μs, the number of 180° pulses is 1000, the repetition time is 1000 ms, the 90° pulse amplitude is -20 dB, and the 180° pulse amplitude is -14 dB; The open porosity is calculated using the following formula: , Wherein, χ is the open porosity of the ceramic silicone foam sheet, and the unit of χ is %; θ is the vacuum volume water absorption of the ceramic silicone foam sheet tested according to the method in Appendix B of GB / T 17794-2021; ρ1 is the density of the ceramic silicone foam sheet tested according to the method in GB / T 6343-2009, and the unit of ρ1 is g / cm 3 ρ s is the density of the surface of the ceramic silicone foam sheet tested according to method A in GB / T 533-2008, ρ s The unit is g / cm 3 .

3. A ceramic silicone foam sheet, wherein: The ceramic silicone foam sheet has a foaming ratio of 3.6-6, a nuclear magnetic resonance transverse relaxation time T2 of 105-130 ms, an open porosity of ≥20%, and a thermal weight loss of 30-50% after ablation at 800° C. for 30 min; The test conditions of the nuclear magnetic resonance transverse relaxation time T2 include: using CPMG pulse sequence excitation, the sensor frequency is 6.0 MHz, the pulse width D=4.5 μs, the echo time TE=120 μs, the number of 180° pulses is 1000, the repetition time is 1000 ms, the 90° pulse amplitude is -20 dB, and the 180° pulse amplitude is -14 dB; The open porosity is calculated using the following formula: , Wherein, χ is the open porosity of the ceramic silicone foam sheet, and the unit of χ is %; θ is the vacuum volume water absorption of the ceramic silicone foam sheet tested according to the method in Appendix B of GB / T 17794-2021; ρ1 is the density of the ceramic silicone foam sheet tested according to the method in GB / T 6343-2009, and the unit of ρ1 is g / cm 3 ρ s is the density of the surface of the ceramic silicone foam sheet tested according to method A in GB / T 533-2008, ρ s The unit is g / cm 3 .

4. The ceramic silicone foam sheet according to claim 3, wherein: The three-point bending strength of the ceramicized silicone foam sheet after being ablated at 800° C. for 30 minutes is ≥8 MPa.

5. The ceramic silicone foam sheet according to claim 3, wherein: The density of the ceramic silicone foam sheet is 200-500 kg / m 3 .

6. The ceramic silicone foam sheet according to claim 3, wherein: The 10% compressive stress of the ceramic silicone foam sheet is 10-20 KPa, and the ratio of the 70% compressive stress to the 10% compressive stress is 20-30.

7. The ceramic silicone foam sheet according to claim 3, wherein: The thickness of the ceramicized silicone foam sheet is 1-15 mm.

8. The ceramic silicone foam sheet according to claim 3, wherein: The average pore diameter of the ceramicized silicone foam sheet is 0.2-1.0 mm.

9. The ceramic silicone foam sheet according to claim 3, wherein: When one side of the ceramic silicone foam sheet is heated at 800°C for 5 minutes, the temperature of the other side thereof is ≤250°C, and the thermal insulation coefficient of the ceramic silicone foam sheet is ≥275°C / mm, wherein the thermal insulation coefficient = (the temperature of one side of the ceramic silicone foam sheet when heated at 800°C for 5 minutes - the temperature of the other side of the ceramic silicone foam sheet) ÷ the thickness of the ceramic silicone foam sheet.

10. The ceramic silicone foam sheet according to claim 3, wherein: After one side of the ceramic silicone foam sheet is ablated by acetylene-oxygen flame at 1300° C. for 10 minutes, no cracks appear on the other side.

11. The ceramic silicone foam sheet according to claim 3, wherein: The Shore A hardness of the ceramicized silicone foam sheet is 5-15°.

Citation Information

Patent Citations

  • Heat storage composition

    CN117321172A

  • Ceramic silicone rubber foam composite material for thermal protection between battery cells

    CN117913427A